Contribution of advanced edge-detection methods of potential field data in the tectono-structural study of the southwestern part of Cameroon - Nzeuga, Alain Rodrigue; Ghomsi, Franck Eitel; Pham, Luan Thanh; Eldosouky, Ahmed M.; Aretouyap, Zakari; Kana, Janvier Domra; Yasmine, Zambou Tsopgni; Fokem, Alpha Baster Kenfack; Nouayou, Robert; Abdelrahman, Kamal; Fnais, Mohammed S.; Andráš, Peter (Frontiers in Earth Science, 2022)
The southwest part of Cameroon is composed of a panoply of geological structures and sedimentary basins whose geological history dates from the Cretaceous, and their establishment would have originated from the opening of the South Atlantic. Among these structures, the most important is the Cameroon Volcanic Line, generally denoted CVL, followed by the southern part of the Central African Shear Zone (CASZ) called the Foumban Shear Zone (FSZ), the Ntem complex, the Benue trough, the northern margin of the Congo Craton and many others. The major structures identified in this part are the results of geodynamic activity between the Oligocene and the recent, to which we can add the volcanism that exists along with the continental limit. 553996 gravity data points obtained from the combination of the XGM2016 model and ETOPO1 were used to highlight the geological structures of southwestern Cameroon. First, we applied the extension method to the Bouguer data to separate the regional and residual data. Then we used a combination of filters to enhance the signature of residual anomalies in southwestern Cameroon. These filters identified various geological structures in the area. Finally, we applied the multi-scale horizontal derivative of the vertical derivative (MSHDVD) to bring out the geological contacts, allowing us to establish the corresponding structural map of the region. The structural map shows that most of the geological boundaries identified in the area are trending in the NE-SW, NW-SE, WSW-ENE, and NNW-SSE directions.